A realist conception of truth - Alston, William P. 1921-2009 (Cornell Univ. Press, 1996)
Alston discusses different realist accounts of truth, examining what they do and do not imply. He distinguishes his version, which he characterizes as "minimalist," from various "deflationary" accounts, all of which deny that asserting the truth of a proposition attributes a property of truth to it. He also examines alethic realism in relation to a variety of metaphysical realisms. Finally, Alston argues for the importance - theoretical and practical - of assessing the truth value of statements, beliefs, and propositions